AeU provides e learning expertise and technology to East Indonesia though UMI - Press, Release (Asia e University, 2011)
Signed a MoU with UMI. Deputy President, Prof. Dr. Hairudin Harun, Hj. Masrurah Mokhtar MA, Rector of UMI.